Effect of halloysite nanotube loading on structure, mechanical and thermal properties of poly (l-lactic acid) / poly-(butylene succinate) blend. (October 2019) - Liu, H Y; Chen, L; Li, W; Wang, K W
Abstract: Poly (l-lactic acid) (PLA)/poly-(butylene succinate) (PBS)/Halloysite Nanotubes (HNT) composites were prepared via melting compounding in a twin-screw extruder. The effects of HNT addition on mechanical properties, thermal properties of PLA/PBS blends were investigated. The structure of ternary composites was studied by Transmission Electron Microscopy (TEM) and the results revealed that a small incorporation of HNT dispersed well in the two polymers. Ternary composites presented improved tensile strength and elongation at break at low loading levels of HNT. Dynamic Mechanical Analysis (DMA) results showed that the addition of HNT significantly increased storage modulus of PLA/PBS composites. The differential scanning calorimetry analysis indicated that HNT can sever as nucleating agent for PLA in ternary composites, which lead to decreased cold crystallization temperature and increased crystallinity of PLA.